Studi Literatur : Perencanaan Arsitektur Fisik Server Big Data Manajemen Global Tapak Suci Putera Muhammadiyah: Literature Study: Physical Architecture Planning of Big Data Server Global Management of Tapak Suci Putera Muhammadiyah. - Rian, Rahmad Al; Syaifullah, Rony (Universitas Muhammadiyah Riau, 2025)
The Indonesian Martial Arts School Tapak Suci Putera Muhammadiyah has been established in 22 countries. In its cadre formation process, Tapak Suci has 15 levels ranging from elementary students to great warriors, where each level will be achieved through a level promotion exam process. In terms of membership age, Tapak Suci has the youngest members at the elementary school level. In the process of building achievements, Tapak Suci regularly holds regional championship events organized by regional leaders, provincial levels organized by regional leaders, national and international levels organized by central leaders. In addition, Tapak Suci members also actively participate in pencak silat events organized by IPSI, Persilat and other pencak silat events. In the process of organizational management, Tapak Suci has a training branch management, regional leaders, regional leaders, regional representatives (overseas) and central leaders. This article is the result of a literature study to determine the server needed by Tapak Suci to carry out global management of its big data so that the development of Tapak Suci's human resources can be monitored in real-time.